Clinicopathological report of 18 cases of women with HIV/AIDS and non–neoplastic cutaneous lesions - Maita Zegarra, Rosa (2001)
OBJECTIVE: To show the clinicopathological features of non-neoplastic cutaneous lesions in women with HIV/AIDS. DESIGN: Descriptive retrospective study. MATERIAL AND METHODS: Biopsies of skin have been taken from 18 women with non–neoplastic cutaneous lesions, and submitted to histopathological and immuno–histochemical studies. RESULTS: Most women were in the age of 20-to-29 years (55,6%), or 30-to-39 years (22,2%), and catalogued as clinical stage B3 (33,3%), or C3 (27,8%). Dermatitis with fibrosis (50%), and granulomatous dermatitis (38,8%) were the commonest cutaneous lesions. We found Candida (44,4%), and Epstein Barr virus (22,2%) as well. CONCLUSIONS: Young women looking for medical care with AIDS indicators, and pruriginous cutaneous lesions, was the predominant picture. Dermatitis with fibrosis and evidence of Candida in cutaneous lesions has been the most frequent diagnosis.